2002
DOI: 10.1023/a:1020763612369
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this paper we examine whether there are differences in the reliability of asset revaluations made by boards of directors versus independent (external) appraisers. We use a sample of recognized Australian asset revaluations. As a first step we examine the determinants of the choice between director-based revaluations and those undertaken by independent appraisers. We find that independent appraisers are more likely to be used for revaluations of land and buildings and directors are more likely for investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In other words, when a financial commodity does not have an active market (lower representational faithfulness), then its fair value is of little relevance (Nelson, 1996). Cotter and Richardson (2002) investigated the means by which the source of fair value information influences its usefulness in Australian companies. They found that when an independent third party (rather than an internal board of directors) reassesses the value of factory buildings and equipment, investors are more likely to treat the findings as reliable.…”
Section: Relationship Between the Methods Used In The Appraisal Of Famentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, when a financial commodity does not have an active market (lower representational faithfulness), then its fair value is of little relevance (Nelson, 1996). Cotter and Richardson (2002) investigated the means by which the source of fair value information influences its usefulness in Australian companies. They found that when an independent third party (rather than an internal board of directors) reassesses the value of factory buildings and equipment, investors are more likely to treat the findings as reliable.…”
Section: Relationship Between the Methods Used In The Appraisal Of Famentioning
confidence: 99%
“…In a review of the literature associated with fair value, Landsman (2007) discovered that most researchers consider fair values (recognized or disclosed) to be useful in investor decisions. However, other studies have found that the degree of usefulness is affected by the number and source of errors in fair value measurement, such as the internal management or external appraisal of corporations (Cotter & Richardson, 2002), and that fair value is obtained from the final price in an active market (Song et al, 2010).…”
Section: Fair Values Under Ifrs 13mentioning
confidence: 99%
“…International standards require the disclosure of information on whether an independent (external) appraiser was involved in the assessment of the fair value of PPE. Cotter and Richardson (2002) found that companies are less likely to involve an external appraiser for plant and equipment (as opposed to property) and attribute this finding to internal appraisers' specific knowledge about the use of these assets. Müller, Riedl, and Sellhorn (2015) highlighted that companies holding an asset for which fair value estimates can be determined less reliably are more likely to engage an external appraiser.…”
Section: Disclosure Requirements Related To Determination Of Fair Value and The Application Of The Revaluation Modelmentioning
confidence: 97%
“…Elde ettikleri bulgular; dış değerleme uzmanlarının yaptıkları değerlemenin nispeten daha güvenilir gerçeğe uygun değer tahminleri sağladığını, yine Big6 denetçileri tarafından denetlenen ve şirket içi değerleme uzmanı kullanan şirketlerde daha doğru gerçeğe uygun değer tahminleri sağlandığını, ancak Big6 denetçileri tarafından denetlenmeyen şirketlerde dış değerleme uzmanı tarafından yapılan değerlemelerin, Big6 denetçileri tarafından denetlenen ve firma içi uzmanların yaptığı değerlemeye göre daha fazla doğruluk taşıdığı sonucuna ulaşmışlardır. Richardson (2002) arazi, bina, ekipman, bitkiler gibi maddi duran varlıkların gerçeğe uygun değer tahminlerinde değerlemenin içsel ve dışsal olarak yapılmasına göre tahminlerin güvenilirliğini araştırırken, düşük değerlemeler yerine (ABD'de bu konuda yeterli derecede çalışma olduğu belirtilmiş) özellikle yüksek değerlemeler üzerine odaklanmışlardır. Daha önceki araştırmalarda, firmaya borç kapasitesindeki artışlar, hisse senedi piyasalarına olumlu sinyaller ve politika maliyetlerdeki düşüşler gibi faydalar sağladığının tespit edilmesi göz önünde bulundurularak hipotezlerini firmaların varlıklarının değerlerini artırmaya yönelik hareket ettikleri varsayımına dayandırmışlardır.…”
Section: Gayri̇menkuller Ve Gerçeğe Uygun Değer üZeri̇ne Yapilan çAli...unclassified